Strain Sensors: A Highly Aligned Nanowire‐Based Strain Sensor for Ultrasensitive Monitoring of Subtle Human Motion (Small 24/2020). Issue 24 (18th June 2020) - Tang, Ning; Zhou, Cheng; Qu, Danyao; Fang, Ye; Zheng, Youbin; Hu, Wenwen; Jin, Ke; Wu, Weiwei; Duan, Xuexin; Haick, Hossam
Abstract : In article number 2001363, Weiwei Wu, Hossam Haick, and co‐workers develop a highly sensitive strain sensor based on nanowires. The nanowires prepared by a capillarity‐inspired imprinting method have an aligned pattern, ensuring the reproducibility of strain sensor fabrication. The nanowire‐based strain sensor exhibits versatile and superior sensing performance for subtle human motion monitoring.